Sexually Transmitted Ischemia, the Other STI: A Case of Gonococcal Endocarditis With Acute Limb Ischemia - Molly Whittaker; Caleb Phillips; Kristen E. Fletcher (Annals of Internal Medicine: Clinical Cases)
A 52-year-old man developed acute pain, numbness, and weakness of his right leg with prodromal fevers and arthralgias. Evaluation revealed mitral valve vegetation and a right femoral artery occlusion, alleviated with thromboembolectomy. Blood cultures finalized without growth, but the thrombus culture grew Neisseria gonorrhea. He was diagnosed with acute limb ischemia due to septic embolization from infective endocarditis. Gonococcal endocarditis occurs in a fraction of disseminated gonococcal infection cases. This pathogen is difficult to culture, complicating diagnosis. Embolic cultures are a valuable tool in identifying gonococcal endocarditis and should be considered in cases of culture-negative endocarditis with septic embolization.